2019
DOI: 10.1111/ppa.12966
|View full text |Cite
|
Sign up to set email alerts
|

Coffee bacterial diseases: a plethora of scientific opportunities

Abstract: Coffee is a very important crop for several tropical countries across different continents. The diseases bacterial halo blight (BHB), bacterial leaf spot (BLS), bacterial leaf blight (BLB) and coffee leaf scorch (CLS), caused by the bacterial pathogens Pseudomonas syringae pv. garcae (Psgc), P. syringae pv. tabaci (Psta), Pseudomonas cichorii (Pch) and Xylella fastidiosa subsp. pauca (Xfp), respectively, cause significant reductions in coffee production, although other minor bacterial diseases have also been r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 142 publications
0
13
0
Order By: Relevance
“…Although Pcg and Pat are part of the P. syringae species complex (Dillon, Thakur, et al, 2019), they belong to different phylogroups, namely phylogroups 3 and 4, respectively, indicating sufficient genomic divergence for species separation (Gomila et al, 2015;Raimundi, 2017). It is estimated that these three pathogens together cause about 70% production losses under nursery and field conditions, mainly in the Brazilian states of Paraná, São Paulo and Minas Gerais (Badel & Zambolim, 2019). Pcg, Pat and Pch cause symptoms on coffee plants often phenotypically indistinguishable and have been shown to be sympatric and to occur in mixed infections (Raimundi, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although Pcg and Pat are part of the P. syringae species complex (Dillon, Thakur, et al, 2019), they belong to different phylogroups, namely phylogroups 3 and 4, respectively, indicating sufficient genomic divergence for species separation (Gomila et al, 2015;Raimundi, 2017). It is estimated that these three pathogens together cause about 70% production losses under nursery and field conditions, mainly in the Brazilian states of Paraná, São Paulo and Minas Gerais (Badel & Zambolim, 2019). Pcg, Pat and Pch cause symptoms on coffee plants often phenotypically indistinguishable and have been shown to be sympatric and to occur in mixed infections (Raimundi, 2013).…”
mentioning
confidence: 99%
“…Even though leaf spot symptoms caused by these three bacterial pathogens cause a great negative impact on coffee production, their genetic and pathogenic variability have not been sufficiently investigated (Badel & Zambolim, 2019). A recent study conducted with strains from Minas Gerais state showed that of the three molecular markers commonly used in repetitive element palindromic PCR (rep-PCR), REP detected genetic variation in Pcg and Pch, ERIC only in Pat and BOX only in Pch (Raimundi, 2017).…”
mentioning
confidence: 99%
“…The insect damage is known to cause an increase in fungal infection [ 8 ]. Bacterial diseases include halo blight, leaf spot, and coffee leaf scorch and are responsible for significant reductions in coffee yields [ 18 ]. Fungal diseases include coffee berry disease, coffee wilt disease, and coffee leaf rust.…”
Section: Optimal Climatic Conditions For Coffeementioning
confidence: 99%
“…Coffee is a crop of significant economic importance in many countries including Brazil, and several factors limit coffee production, including fungal and bacterial diseases [ 17 ]. The bacterial halo blight of coffee (BHB) caused by Pseudomonas syringae pv .…”
Section: Introductionmentioning
confidence: 99%
“…The bacterial halo blight of coffee (BHB) caused by Pseudomonas syringae pv . garcae [ 18 , 19 ], is a disease that has caused losses in nurseries and fields established in regions subjected to strong winds, mild temperatures, and frequent and well-distributed rains [ 17 , 20 ]. Among the coffee ( Coffea arabica L.) cultivars planted in Brazil, the Mundo Novo 376/4 cultivar corresponds to almost half of the planted area.…”
Section: Introductionmentioning
confidence: 99%